The Dawn Angiosperms Uncovering the Origin of Flowering Plants - Wang, Xin.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This book, besides providing necessary background information and discussions, focuses on the earliest angiosperms: namely those more than 125 million years old. Currently 125 million year old angiosperms, are the oldest to be found - especially in the eyes of European scholars. It proceeds by introducing several interesting angiosperms from the Jurassic and early Cretaceous, including Schmeissneria (early-middle Jurassic, 160-199 million years old (Ma)), Xingxueanthus (middle Jurassic, 160 Ma), Solaranthus (middle Jurassic, 164 Ma), Callianthus (early Cretaceous, 125 Ma), Chaoyangia (early Cretaceous, 125 Ma), Archaefructus (early Cretaceous, 125 Ma), Sinocarpus (early Cretaceous, 125 Ma). Others are currently being processed. These fossils, most of which have hitherto not been published,will uncover many unknown aspects of early angiosperms, and help to solve the mystery surrounding their origin.
Suggested Angiosperm Ancestors -- Angiosperms: Characters and Criteria -- Background for the Plant Fossils -- Flowers from the Early Cretaceous -- Flower-Related Fossils from the Jurassic -- Trace of Possible Angiosperms in the Jurassic -- Making of the Flower -- General Conclusions.
Keywords: Geography; Life sciences; Earth Sciences; Biogeosciences